A brief measure of student perceptions of the educational value of research participation - Roberts, Lynne; Allen, Peter (John Wiley & Sons Ltd., 2013)
Despite the continued reliance on undergraduate students as research participants, there is an absence of valid, reliable measures of student perceptions of educational gains from research participation. In this article, we present two studies outlining the development and initial validation of a new measure, the student perceptions of the educational value of research participation scale. In Study One a pool of 28 items was developed from previous qualitative research and administered to a convenience sample of 68 Australian university student volunteers. Following principal axis factoring, a seven-item unidimensional scale with good internal reliability (α = .82) was developed and validated against an existing measure of reactions to research participation. In Study Two, 104 members of a second-year undergraduate psychology participant pool completed the measure. Confirmatory factor analysis supported a higher order two-factor model (overall α = .82). Across both volunteer and participant pool samples, the educational value of research participation was rated more highly than the costs of research participation (emotional reactions and drawbacks of participating), indicating a positive cost–benefit ratio of research participation. This brief, internally reliable measure can be used in assessing students' perceptions of educational gain in both individual research projects and across research projects.